2018
DOI: 10.1002/dmrr.2979
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and mortality in patients with and without diabetes mellitus

Abstract: In hospitalized patients with and without DM, there was an inverse association between BMI and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…showed that normal weight individuals with T2DM had higher odds for all‐cause mortality compared with subjects with a BMI ≥25 kg/m 2 237 . The finding that a higher BMI (even in those classified as having severe obesity) was protective against all‐cause mortality in patients with T2DM has also been replicated across different ethnicities 238 . Interestingly, individuals within the underweight or near‐normal BMI categories were observed to have the highest risk compared with all other BMI categories 238 .…”
Section: Natural Course and Clinical Implications Of Mho And Muhnwmentioning
confidence: 83%
See 2 more Smart Citations
“…showed that normal weight individuals with T2DM had higher odds for all‐cause mortality compared with subjects with a BMI ≥25 kg/m 2 237 . The finding that a higher BMI (even in those classified as having severe obesity) was protective against all‐cause mortality in patients with T2DM has also been replicated across different ethnicities 238 . Interestingly, individuals within the underweight or near‐normal BMI categories were observed to have the highest risk compared with all other BMI categories 238 .…”
Section: Natural Course and Clinical Implications Of Mho And Muhnwmentioning
confidence: 83%
“…238 Interestingly, individuals within the underweight or near-normal BMI categories were observed to have the highest risk compared with all other BMI categories. 238 These data support the obesity paradox (i.e. the reduced mortality risk observed in people with obesity as compared to normal weight) at least within subjects with diabetes.…”
Section: Zhang Et Al Reported the Highest Transitions From Muhnw Tomentioning
confidence: 96%
See 1 more Smart Citation
“…Initial assessment of the patients by history and clinical physical examination was performed and listed in the performed data compilation sheet. Data was collected through routine examination (RE) urine samples to assess proteinuria for preeclampsia while body weights were measured in kilograms and heights in centimeters for determination of obesity according to body mass index (BMI) classification that for Normal is (18.5-24.9), over 18 weight (25-29.9) and obese (30-34.9). Data was analyzed by using Statistical Package for Social Sciences (SPSS) Version 20; frequencies and percentages were taken and chi square test was applied to find association between obesity, preeclampsia and GDM.…”
Section: Methodsmentioning
confidence: 99%